Legal Analysis Of Judge's Decision On The Imposition Of Criminal Sanctions For Placement Of Illegal Indonesian Migrant Workers Study Of Decision No. 107/PID.SUS/2024/PN RHL - Bambang Hermanto; Sriono Sriono; Nimrot Siahaan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
The method used in this study is normative legal research, namely research on problems by looking at the sources of applicable regulations related to the title of Legal Analysis of Judge's Decisions Regarding the Imposition of Criminal Sanctions for the Placement of Illegal Indonesian Migrant Workers Study of Decision No. 107 / PID.SUS / 2024 / PN RHL. The legal policy stipulated in this decision is based on Article 81 of Law of the Republic of Indonesia Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers, as well as other relevant laws and regulations, so that the results of the decision try and determine that the defendant has been proven legally and convincingly guilty of committing the crime of "An individual who carries out the placement of Indonesian Migrant Workers". Sentencing the defendants to a criminal sentence, therefore, with imprisonment for 8 (eight) months each. In the theory of punishment, it must be guided by the basic values ​​(grund norm) of the law itself which contain elements of justice, usefulness, and legal certainty. According to the author, in decision No. 107/PID.SUS/2024/PN RHL already contains an element of justice, because the judge does not favor one party and the punishment for the perpetrators of the crime is in accordance with the laws and regulations. The element of benefit is that the sentence imposed can have a deterrent effect on perpetrators of crimes who place Indonesian Migrant Illegal Workers illegally, also as an appeal to prospective Indonesian Migrant Illegal Workers to be more careful in choosing a company that places Indonesian Migrant Illegal Workers